Ethical Challenges to Respecting and Meeting Patients’ Requests: Lessons from Providing Palliative Care for Coronavirus Disease 2019 Patients - John Weru (Palliative Medicine and Hospice Care, 2021)
The World Health Organization (WHO) defines palliative care as: “an approach that improves the quality of life of patients and their families facing the problem associated with life-threatening illness, through the prevention and relief of suffering by means of early identification and impeccable assessment and treatment of pain and other problems, physical, psycho-social and spiritual.